Keeping Jigsaws Connected - Johan Oppen (Communications - Scientific letters of the University of Zilina, 2013)
This paper describes a combinatorial problem where the idea is to find out in how many ways a jigsaw puzzle can be built, piece by piece, in such a way that it stays connected at all times during the building phase. Computational methods, both exact and approximate, to count the number of such connected sequences are presented.